Nonsurgical OrthodonticTreatment of Anterior Open Bite in Adult: A Case Report - Leela-adisorn, Niramon (Journal of Health Science of Thailand, 2018)
The treatment of anterior open bite especially in adult cases caused from skeletal structure and myofunction is one of the most arduous procedures in orthodontics. An appropriate treatment plan specific to each case with proper retention is essential to the outcome. This article reports the treatment of anterior open bite in adults caused from skeletal structure, dentoalveolar, muscular functions and oral habits utilising only orthodontic procedures. The treatment plan dictated the extraction of all first premolar teeth, followed by fixed appliance. The retention period prescribed the use of wrapped around retainers and myofunctional exercise to gain the equilibrium of force from mouth cheek and tongue. The process enabled the result of treatment to remain stable even 5 years after the treatment.